Building Brand Image of Madrasah Institutions through Digital Media Platform - Abu Hasan Agus R; Fitrotun Nafi’ah (Journal of Educational Management Research, 2024)
The development of digital technology encourages educational institutions, including madrasas, to utilize digital platforms in building their brand image. This study aims to examine the role of digital media in building the brand image of Islamic-based madrasas, focusing on two madrasas that implement digital tahfidz and social media as branding strategies. The study uses a qualitative approach with in-depth interviews and observations of the use of platforms such as YouTube and social media. The findings show that digital media is effective in introducing and strengthening the brand image of madrasas, increasing visibility, and attracting public interest. The support of madrasah policies and the use of technology by managers play an important role in the success of this digital branding. Overall, the results of this study indicate that the use of digital platforms can build a positive image of madrasas, expand audience reach, and increase the attractiveness of madrasas in the era of digital transformation. The contribution of this study is to provide an understanding of the importance of digital branding strategies for madrasas in improving their brand image.